Association of Major Dietary Protein Sources with All-cause and Cause-specific Mortality: The Women's Health Initiative (FS03-08-19). (13th June 2019) - Sun, Yangbo; Liu, Buyun; Snetselaar, Linda; Wallace, Robert; Shadyab, Aladdin; Kroenke, Candyce; Haring, Bernhard; Howard, Barbara; Shikany, James; Valdiviezo, Carolina; Bao, Wei
Abstract: Objectives: The objective was to examine the prospective association of major dietary protein sources with all-cause and cause-specific mortality in U.S. women. Methods: We included 127, 495 postmenopausal women aged 50 to 79 years old at study entry who were enrolled between 1993 and 1998 in the Women's Health Initiative from September 1993, and followed through February 2017. Prospective cohort study. We used multivariable Cox proportional hazards models to estimate adjusted HRs of all cause, cardiovascular, cancer and dementia mortality in relation to major protein sources. Results: During 2, 302, 230 person-years of follow-up, 35, 043 deaths occurred. Total protein or animal protein intake was not significantly associated with all-cause or cause-specific mortality. Plant protein intake was inversely associated with all-cause, CVD and dementia mortality, with multivariable-adjusted HRs (95% CIs), comparing the higher with the lowest quintile, as 0.91 (0.86, 0.95), 0.87 (0.79, 0.95), and 0.81 (0.70, 0.94), respectively. Substituting 5% energy from animal protein with plant protein was associated with a 13% lower risk of all-cause mortality. For major protein sources, consumption of unprocessed red meat, processed red meat, and eggs, was associated with higher risk of all-cause mortality, with multivariable-adjusted HRs (95% CIs), comparing the higher with the lowest quintile, as 1.07 (1.03, 1.11), 1.07 (1.03, 1.11), and 1.14 (1.10, 1.18), respectively, while nut consumption was associated with a slightly lower risk of all-cause mortality, with multivariable-adjusted HRs (95% CIs), comparing the higher with the lowest quintile, as 0.97 (0.93, 0.99). Substituting 4 ounce equivalent/day of total red meat with poultry, fish/shellfish, or nuts, was associated with a 8%, a 12%, and a 12% lower risk of all-cause mortality, respectively. Conclusions: Different dietary protein sources have varying associations with lower all-cause, CVD and dementia mortality. Substituting total red meat with poultry, fish/shellfish, or nuts was associated with lower risk of all-cause mortality. Funding Sources: NIH.